Extra‐Judicial Conferences in Child Welfare Cases: Reassessing their Role and Implications for Practice and Policy. (March 2017) - Finck, Kara R.
Abstract: Child welfare agencies increasingly utilize family team decision‐making conferences in cases where there is a pending child protection matter in family court. The simultaneous proceedings present critical questions for all practitioners and judges about the relationship between the court and the agency, and implications for the rights of parents and children. This article discusses the critical tensions raised when the agency pursues extra‐judicial conferences in the absence of coordination with and recognition of the court process, including expectations of confidentiality, the role of attorneys in conferences and the perception of fairness in both forums.